Wednesday

July 30, 2014

July 30, 2014

Posted by **olek** on Thursday, May 12, 2011 at 7:31pm.

ln(e^x − e ^−x) (x > 0).

By applying in turn the Composite and Quotient Rules, calculate

that gives an expression for each of the following.

1. f!(x)

2. f!!(x)

- maths -
**Mgraph**, Thursday, May 12, 2011 at 8:50pmf!(x)-? maybe f'(x)

**Related Questions**

biology - Given the part of the molecule shown below, can the underlined atom ...

maths - f(x)=ln(e^x-e^-x), x>0 By applying in turn the Composite and Quotient...

maths - f(x)=ln(e^x-e^-x), x>0 By applying in turn the Composite and Quotient...

maths - f(x)=ln(e^x-e^-x), x>0 By applying in turn the Composite and Quotient...

maths - f(x)=ln(e^x-e^-x), x>0 By applying in turn the Composite and Quotient...

maths - The method for completing the square can be used to write the expression...

Alg - Given f(x) = 2x^2 – 2 and g(x) = –2x + 4, find the following. (f − g...

Math - First, give the technology formula for the given function and then use ...

Math - PreCalc (12th Grade) - If Sn = 1 + 6 + 11 + 16 + 21 + 26...... where an...

Algebra - Given f(x) = 2x − 1 and g(x) = 4x − 4, evaluate the ...